Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

Human footprints in the Global South accelerate biomass carbon loss in ecologically sensitive regions - Mengqing Geng; Xuecao Li; Haowei Mu; Guojiang Yu; Li Chai; Zhongwen Yang; Haimeng Liu; Jianxi Huang; Han Liu; Zhengshan Ju (Global Change Biology, 2023)
Human activities have placed significant pressure on the terrestrial biosphere, leading to ecosystem degradation and carbon losses. However, the full impact of these activities on terrestrial biomass carbon remains unexplored. In this study, we examined changes in global human footprint (HFP) and human‐induced aboveground biomass carbon (AGBC) losses from 2000 to 2018. Our findings show an increasing trend in HFP globally, resulting in the conversion of wilderness areas to highly modified regions. These changes have altered global biomes' habitats, particularly in tropical and subtropical regions. We also found accelerated AGBC loss driven by HFP expansion, with a total loss of 19.99 ± 0.196 PgC from 2000 to 2018, especially in tropical regions. Additionally, AGBC is more vulnerable in the Global South than in the Global North. Human activities threaten natural habitats, resulting in increasing AGBC loss even in strictly protected areas. Therefore, scientifically guided planning of future human activities is crucial to protect half of Earth through mitigation and adaptation under future risks of climate change and global urbanization.